CULTURAL VALUES IN ORAL LITERATURE OF KRINOK: ANTROPOLINGUISTIC STUDY - Arie Sugiyartati; Burhanuddin Arafah; Fathu Rahman; Mustafa Makka (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This study aimed to examine the uniqueness of the Krinok oral literary structure, the meaning of traditional and cultural values, and the variety of cultural values possessed by the Batin people in Bungo Regency, Jambi, which focused on the Krinok speakers in the area. This research applied qualitative approach using anthropolinguistic studies following Alessando Duranti (2001) and William A. Foley (1997). Data collection was carried out by means of interviews and literature study. Interviews were carried out when meeting with informants of Krinok and the interviews were recorded. The results showed that the uniqueness of Krinok oral literature lies in the structure of the pantun ‘a typical Indonesian four-line verse’ which has a high pitch at the beginning of the speech, the repetition of the first and second verse and all of which show all the competencies, indexicality, performance that exist in Duranti's anthropolinguistic theory. There are also cultural values, as stated by Djamaris in his theory (1993: 2-3), the concept of cultural values in human relations with God, cultural values of human relations with nature, cultural values of human relations with society, cultural values of human relations with other humans, and cultural values of human relations with themselves.